2017
DOI: 10.1002/jmri.25591
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the influence of respiration and cardiac pulsations on cerebrospinal fluid dynamics using real‐time phase‐contrast MRI

Abstract: 1 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:431-439.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(195 citation statements)
references
References 34 publications
8
185
0
2
Order By: Relevance
“…Additionally, in vitro studies have been performed by our group to quantify the reliability of MRI for CSF geometric and flow measurements. Yildiz et al 2017, found a CV of 4.8% for peak CSF flow at a single location [31] and Thyagaraj et al 2017, found a an average CV of 8% for peak CSF flow across several locations [32]. Geometric reconstruction was also analyzed by Thyagaraj et al 2017, and found to be in good agreement with the digital.…”
Section: Reliability Of Mri Based Measurements Of Csf Hydrodynamicsmentioning
confidence: 92%
“…Additionally, in vitro studies have been performed by our group to quantify the reliability of MRI for CSF geometric and flow measurements. Yildiz et al 2017, found a CV of 4.8% for peak CSF flow at a single location [31] and Thyagaraj et al 2017, found a an average CV of 8% for peak CSF flow across several locations [32]. Geometric reconstruction was also analyzed by Thyagaraj et al 2017, and found to be in good agreement with the digital.…”
Section: Reliability Of Mri Based Measurements Of Csf Hydrodynamicsmentioning
confidence: 92%
“…Our modeling approach did not include flow oscillations within the ventricles [69,70] or a respiratory component of CSF pulsations [71][72][73] because the MRI scanning time did not allow measurement of these parameters in addition to the other parameters used to formulate the model. Additionally, the presented model used a rigid material in which boundary motion of the dura was not prescribed [25].…”
Section: Limitationsmentioning
confidence: 99%
“…Other investigators used magnitude intensity variations in real‐time MRI to demonstrate that respiration may also influence CSF hydrodynamics, especially during deep breathing . This was confirmed by real‐time phase‐contrast echo‐planar imaging (PCEPI) applications in the brain and cranium, the foramen magnum and real‐time phase‐contrast combined with radial gradient echo acquisitions in different cervical and thoracic levels …”
Section: Introductionmentioning
confidence: 91%